The Level of Creative Teaching Skills among Faculty Members in Algerian Universities - Zohra Ali Lassoued (University of Science and Technology, Yemen, 2018)
The study aimed to identify the level of possessing creative teaching skills among a sample of faculty members in Algerian universities and to find out whether there were differences in the respondents' assessment of the level of having creative teaching skills due to gender, years of service and academic rank. The study followed the descriptive analytical method. The sample consisted of (260) faculty members of four Algerian universities that, were selected in a simple random way. A questionnaire designed by the researcher was used to measure the skills of creative teaching. The results showed that the assessment of faculty members in Algerian universities for their creative teaching skills was low, with relative weight of (42.46%). The results also showed that there were statistically significant differences between the average scores of the sample members of the level of creative teaching skills attributed to the gender variable in favor of the female members, and the academic specialization in favor of human sciences. There were no differences of statistical significance between the average scores of the sample members in the level of creative teaching skills attributed to the years of service and academic rank. The study recommended that the university administration should take care of on-service training to faculty members in the field of creative teaching in order to help them develop their teaching skills. Keywords: Teaching skills, Creative teaching, Faculty members.